Cardiovascular mortality in patients with advanced chronic kidney disease with and without diabetes: a nationwide cohort study - Dea Haagensen Kofod; Nicholas Carlson; Ellen Freese Ballegaard; Thomas Peter Almdal; Christian Torp-Pedersen; Gunnar Gislason; Jesper Hastrup Svendsen; Bo Feldt-Rasmussen; Mads Hornum (Cardiovascular Diabetology, 2023)
Abstract Background Cardiovascular mortality and the impact of cardiac risk factors in advanced chronic kidney disease (CKD) remain poorly investigated. We examined the risk of cardiovascular mortality in patients with advanced CKD with and without diabetes as well as the impact of albuminuria, plasma hemoglobin, and plasma low-density lipoprotein (LDL) cholesterol levels. Methods In a Danish nationwide registry-based cohort study, we identified persons aged ≥ 18 years with an estimated glomerular filtration rate < 30 mL/min/1.73m2 between 2002 and 2018. Patients with advanced CKD were age- and sex-matched with four individuals from the general Danish population. Cause-specific Cox regression models were used to estimate the 1-year risk of cardiovascular mortality standardized to the distribution of risk factors in the cohort. Results We included 138,583 patients with advanced CKD of whom 32,698 had diabetes. The standardized 1-year risk of cardiovascular mortality was 9.8% (95% CI 9.6–10.0) and 7.4% (95% CI 7.3–7.5) for patients with and without diabetes, respectively, versus 3.1% (95% CI 3.1–3.1) in the matched cohort. 1-year cardiovascular mortality risks were 1.1- to 2.8-fold higher for patients with diabetes compared with those without diabetes across the range of advanced CKD stages and age groups. Albuminuria and anemia were associated with increased cardiovascular mortality risk regardless of diabetes status. LDL-cholesterol was inversely associated with cardiovascular mortality risk in patients without diabetes, while there was no clear association in patients with diabetes. Conclusions Diabetes, albuminuria, and anemia remained important risk factors of cardiovascular mortality whereas our data suggest a limitation of LDL-cholesterol as a predictor of cardiovascular mortality in advanced CKD.